Localization of Directional Sound Sources Supported by A Priori Information of the Acoustic Environment. (27th November 2007) - Fodróczi Fodróczi, Zoltán Zoltán; Radványi Radványi, András András
Abstract : Speaker localization with microphone arrays has received significant attention in the past decade as a means for automated speaker tracking of individuals in a closed space for videoconferencing systems, directed speech capture systems, and surveillance systems. Traditional techniques are based on estimating the relative time difference of arrivals (TDOA) between different channels, by utilizing crosscorrelation function. As we show in the context of speaker localization, these estimates yield poor results, due to the joint effect of reverberation and the directivity of sound sources. In this paper, we present a novel method that utilizes a priori acoustic information of the monitored region, which makes it possible to localize directional sound sources by taking the effect of reverberation into account. The proposed method shows significant improvement of performance compared with traditional methods in "noise-free" condition. Further work is required to extend its capabilities to noisy environments.